Comparison of the responsiveness of the Utrecht Scale for Evaluation of Rehabilitation (USER) and the Barthel Index in stroke patients. (October 2019) - van Meijeren-Pont, Winke; Volker, Gerard; Vliet Vlieland, Thea; Goossens, Paulien
Objective: To compare the responsiveness of the Utrecht Scale for Evaluation of Rehabilitation (USER) to the responsiveness of the Barthel Index in stroke patients in an inpatient rehabilitation facility. Design: Observational study. Setting: Inpatient rehabilitation facility. Subjects: Consecutive stroke patients admitted for clinical rehabilitation. Interventions: Not applicable. Main measures: The USER and the Barthel Index were administered by a nurse at admission and discharge. The Effect Size and Standardized Response Mean (SRM) were calculated as measures of responsiveness. Results: From 198 (78%) of the 254 patients who were included in the study period, both admission and discharge data were available. At admission the mean score of the USER subscale Functional independence was 43.1 ( SD  = 18.9) and at discharge the mean score was 59.3 ( SD  = 13.8). The mean score of the Barthel Index at admission was 13.3 ( SD  = 5.4) and at discharge 18.4 ( SD  = 3.3). The Effect Size of the USER subscales Mobility, Self-care, Cognitive functioning, Pain, Fatigue and Mood were 0.85, 0.77, 0.48, 0.19, 0.40 and 0.28, respectively, and of the Barthel Index 0.94. The results for the SRM were in the same range. Conclusion: In inpatient rehabilitation after stroke, the USER was less responsive than the Barthel Index.